Pertumbuhan dan Produksi Bibit Tanaman Tebu (Saccharum officinarum L.) Jenis Bud Sett pada Berbagai Masa Tunda Penanaman - Zaqyah, Irene; Adimiharja, Jamaludin; Wahyuni, Reza; Aprianto, Eko (J-Plantasimbiosa, 2024)
Bud sett is one type of sugarcane planting material that is efficient in terms of size, allowing the distribution process in large quantities from variety producers to users. However, its smaller size than mule-shaped planting material will cause the freshness of bud sett planting material to decrease more quickly during storage due to the delayed planting period. The purpose of this study was to determine the impact of delayed planting at various storage periods of bud sett sugarcane seeds on the initial growth and production of sugarcane seeds. This study used a Randomized Block Design with 3 replications. The treatment of delayed planting period was 5 levels, namely without storage period (T0), storage period 1 x 24 hours (T1), storage period 2 x 24 hours (T2), storage period 3 x 24 hours (T3) and storage period 4 x 24 hours jam (T4). The data were analyzed variously and tested for the mean value using the Least Significant Difference (LSD) test at the 5% level. The results showed that the weight and germination of bud setts decreased with increasing length of the delayed planting period. In general, the storage period for bud sett seeds does not have a significant effect on seedling growth and seedling production.